Redes del cuidado : ética del destino compartido en las madres comunitarias antioqueñas (2013)
ABSTRACT: In this article I discuss the problem of the communal mothers’ support networks. Objective: to identify the significance that the communal mothers give to self-care in relation to the care promoted in the children from the communal homes in their care. Scope: to enhance the understanding of the care practices among the communal mothers from the city of Medellin. Methodology: With a qualitative approach and a phenomenological-hermeneuticalmethodology, 30 communal mothers from 6 Antioquia municipalities participated in the study,they were interviewed in depth and participated in focal groups. Results: Each communal mother constructs her own care network, whose axis of sense is the care given to children. Findings: (1) the care of these children requires a care network; (2) this is a subjective construction; (3) when a woman becomes a communal